Menumbuhkan Cinta Hari Besar Islam Bagi Anak Usia Dini Melalui Pekan Muharram di Desa Pagar Jati, Kecamatan Semidang Lagan, Kabupaten Bengkulu Tengah - Nurmaniasari, Melinda; Mardahliah, Sherli; Aprisa, Hesti (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Developing a generation of Muslims who have noble, intelligent and creative character from an early age is a strategic effort to form individuals who excel and contribute positively to society. Education based on Islamic values plays an important role in shaping children’s character and morals, so that they are able to become individuals with noble morals. Apart from that, learning Having noble, intelligent and creative character from an early age is needed to stimulate children’s intelligence, both from an intellectual, emotional and spiritual perspective. Through a holistic approach, which includes aspects of religious education, academic intelligence and creative skills, it is hoped that it will be able to produce a young generation that is strong and highly competitive in the era of globalization. This research highlights the important role of the family, school and social environment in supporting the process of forming children’s character and intelligence, both from an intellectual, emotional and spiritual perspective. Through a holistic approach, which includes aspects of religious education, academic intelligence and creative skills, it is hoped that it will be able to produce a young generation that is strong and highly competitive in the era of globalization. This research highlights the important role of the family, school and social environment in supporting the process of forming children’s character and intelligence, and offers effective strategies that can be implemented to achieve this goal.